A fiscalização pública de obras particulares em Santos - Barbosa, Maria Valquíria de Souza (Universidade Federal de São Carlos, 2004)
In today s urban cities we can observe the existence of various activities interacting, dividing or struggling for the same space. The co-existence of commercial, institutional, residential or leisure activities requires the presence of urban regulations which can guarantee the quality of urban space. Many times, urban laws do exist, but are not respected. Several times they are infringed, and with the frequent existence of amnesty laws, what was once illegitimate becomes legal. The existence of urban laws and regulations is not a guarantee of quality urban space. City council -- who should be responsible for enforcing and creating urban laws, business men, contractors, technicians and general population are all responsible for not abiding to the rules. For various different reasons, each sector tries to defend what is of their own interest, caring vary little for the greater good of the community. Public inspection in the private construction sector ends up being the most responsible for urban regulation breach, but the responsibility is of the entire community.
Keywords: Planejamento urbano; Obras particulares; Obras -fiscalização; Legislação urbanística; Lei de anistia; Santos (SP); ENGENHARIAS